ANALISIS PELAYANAN PUBLIK YANG BERPENGARUH TERHADAP KINERJA PEGAWAI KANTOR SAMSAT WILAYAH I MAKASSAR - Rosnidawati Rosnidawati; H. Ahmad Musseng; Jamil Thalib (Jurnal Bisnis dan Kewirausahaan, 2018)
The aims of the research are (i) to know and to analyze a simple, on time, transparency, fairness, and economic public service which affected the performance of employees at Samsat Area I Makassar, (ii) to know and to analyze public service which dominantly affected the employees performance at Samsat Area I Makassar. This researched was conducted in Samsat Area I Makassar, 71 respondents were taken as sample and population. The analysis used in this research are descriptive and quantitative. The descriptive analysis is aimed at explaining data and description of research while quantitative analysis used multiple linear regression. The result proved that public service which in simple, on time, transparency, fairness economic, positively and significantly affected the employees of performance at Samsat Area I Makassar. In partially, the public service gave a positive and significant influence to the employees performance at Samsat Area I Makassar as follows: (i) simple service gave a significant influence on suitable procedure; (ii) on time service gave significant influence on the performance which is suitable with community; (iii) transparency service gave significant influence on the performance based on information transparency, exactly and certainty; (iv) fairness service gave significant influence on the performance which is fair, indiscriminative, and empathy; and (v) economic service gave significant influence on the performance in accordance with standard cost. The result of the research showed that economic public service which is dominantly affected on the performance of employees at Samsat Area I Makassar.